Transcriptional regulators of human oncoviruses: structural and functional implications for anticancer therapy - Nečasová, Ivona; Stojaspal, Martin; Motyčáková, Edita; Brom, Tomáš; Janovič, Tomáš; Hofr, Ctirad (NAR cancer, 2022)
Transcription is often the first biosynthetic event of viral infection. Viruses produce preferentially viral transcriptional regulators (vTRs) essential for expressing viral genes and regulating essential host cell proteins to enable viral genome replication. As vTRs are unique viral proteins that promote the transcription of viral nucleic acid, vTRs interact with host proteins to suppress detection and immune reactions to viral infection. Thus, vTRs are promising therapeutic targets that are sequentially and structurally distinct from host cell proteins. Here, we review vTRs of three human oncoviruses: HBx of hepatitis B virus, HBZ of human T-lymphotropic virus type 1, and Rta of Epstein-Barr virus. We present three cunningly exciting and dangerous transcription strategies that make viral infections so efficient. We use available structural and functional knowledge to critically examine the potential of vTRs as new antiviral-anticancer therapy targets. For each oncovirus, we describe (i) the strategy of viral genome transcription; (ii) vTRs' structure and binding partners essential for transcription regulation; and (iii) advantages and challenges of vTR targeting in antiviral therapies. We discuss the implications of vTR regulation for oncogenesis and perspectives on developing novel antiviral and anticancer strategies.